2018
DOI: 10.3892/mmr.2018.9618
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of LOX‑5 and COX‑2 expression with inflammatory pathology and clinical features of adenomyosis

Abstract: Adenomyosis is a common benign disease of women of childbearing age. The typical clinical features are prolonged menstruation, menorrhagia and ingravescent dysmenorrhea. In the present study, the severity of dysmenorrhea was assessed using the visual analogue scale system as follows: 0, No pain; 1-3, minimal pain; 4-6, moderate pain; and 7-10, severe pain. Menstrual blood loss was evaluated using the pictorial blood loss assessment chart (PBAC). Menorrhagia was defined as excessive menstrual blood loss >80 ml … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 17 publications
3
10
0
1
Order By: Relevance
“…CMI-related terms recurred in multiple comparisons between groups and the enrichment of upregulated DEGs, which suggested that canceration, cell motility and in ammation may play an important role in the process of AM. The study of AM suggested that in ammation accumulated in the eutopic endometrium sample compared with in the control sample [40,46], which was supported by the results of the comparison between the AM_EM and AM_CTRL groups in the present study (Additional le 1: Figure S4B, D). In addition, the in ammatory terms were further enriched in the AM_EC group; however, the proportion of in ammation-related subcluster 4 cells in the epithelial cell group was higher in the AM_EM sample than in the AM_EC sample, which may facilitate disease progression because in ammation can promote cell migration and invasion [47].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…CMI-related terms recurred in multiple comparisons between groups and the enrichment of upregulated DEGs, which suggested that canceration, cell motility and in ammation may play an important role in the process of AM. The study of AM suggested that in ammation accumulated in the eutopic endometrium sample compared with in the control sample [40,46], which was supported by the results of the comparison between the AM_EM and AM_CTRL groups in the present study (Additional le 1: Figure S4B, D). In addition, the in ammatory terms were further enriched in the AM_EC group; however, the proportion of in ammation-related subcluster 4 cells in the epithelial cell group was higher in the AM_EM sample than in the AM_EC sample, which may facilitate disease progression because in ammation can promote cell migration and invasion [47].…”
Section: Discussionsupporting
confidence: 87%
“…The endometrium directly invaded the myometrium, and misplaced pluripotent Müllerian remnants were proposed to cause the pathogenesis of AM [6]. Moreover, in ammatory factors, such as LOX5 and COX2, are related to dysmenorrhoea and menstruation [40], and it has also been reported that angiogenesis participates in the pathophysiology of abnormal uterine bleeding and subfertility in AM [3]. Nevertheless, the precise pathogenesis of AM is still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes have been widely explored for being involved in pathologies such as asthma, anaphylactic shock and cardiovascular diseases. Among them, 5-LOX is the most studied because it is present in inflammatory cells (leukocytes, polymorphonuclear cells, basophils, mast cells, eosinophils, and macrophages) [ 41 , 42 ].…”
Section: The Role Of Thiophene Derivatives In Inflammationmentioning
confidence: 99%
“…This results in a proteasomal degradation of IκB protein, while NF-κB can then translocate to the nucleus, binding DNA and activating the transcription of some targeted genes for cytokines, such as tumor necrosis factor-α (TNF-α) and interleukins (IL) (IL-1β and IL-6), as well as the production of several enzymes including cyclooxygenase (COX) and lipoxygenase (LOX) ( Figure 4 ) [ 71 , 72 , 73 ]. These latter enzymes have a key role in the inflammatory process through the transformation of the arachidonic acid released from the phospholipid membrane into a spectrum of pro-inflammatory bioactive mediators including prostanoids and leukotrienes, which act by enhancing edema formation, increasing vascular permeability and leukocytes’ infiltration into the injured tissue [ 74 , 75 , 76 ].…”
Section: Opuntia Sp In Inflammationmentioning
confidence: 99%